2000
DOI: 10.1093/gerona/55.3.b152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strength Training and Detraining on Muscle Quality: Age and Gender Comparisons

Abstract: Maximal force production per unit of muscle mass (muscle quality, or MQ) has been used to describe the relative contribution of non-muscle-mass components to the changes in strength with age and strength training (ST). To compare the influence of age and gender on MQ response to ST and detraining, 11 young men (20-30 years), nine young women (20-30 years), 11 older men (65-75 years), and 11 older women (65-75 years), were assessed for quadriceps MQ at baseline, after 9 weeks of ST, and after 31 weeks of detrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
117
5
10

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 22 publications
15
117
5
10
Order By: Relevance
“…As mentioned, several interruptions occurred along the intervention, but their influence on the results was not determined because the participants' physical activity during this period was not assessed. Likewise, in spite of other studies having reported the permanence of changes achieved by the programs for long periods of time after their completion 55,56 , a follow-up investigation was not carried out after this program, which precludes any knowledge about how the changes found in participants' physical capacity evolved. Finally, the absence of a control group reduces the internal validity of the present study, although randomized controlled trials cannot be considered the only source of scientific evidence in complex interventions 57 and other studies with similar designs have shown their ability to identify effects in the same target population 49,58 .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, several interruptions occurred along the intervention, but their influence on the results was not determined because the participants' physical activity during this period was not assessed. Likewise, in spite of other studies having reported the permanence of changes achieved by the programs for long periods of time after their completion 55,56 , a follow-up investigation was not carried out after this program, which precludes any knowledge about how the changes found in participants' physical capacity evolved. Finally, the absence of a control group reduces the internal validity of the present study, although randomized controlled trials cannot be considered the only source of scientific evidence in complex interventions 57 and other studies with similar designs have shown their ability to identify effects in the same target population 49,58 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its general effectiveness, the degree of RT-induced muscle hypertrophy varies across different age and gender groups Tracy et al, 1999;Welle et al, 1996). We and others have previously observed a blunted hypertrophic response in older females following long-term RT (Bamman et al, 2003;Ivey et al, 2000;Kosek et al, 2006). Although the underlying mechanism has not been well-defined, the divergent extent of hypertrophy in old females may occur in part from reduced myogenic aptitude (Gallegly et al, 2004;Leiter et al, 2011), which could conceivably impair the regenerative processes activated in response to mechanical loading.…”
Section: Introductionmentioning
confidence: 95%
“…These physiological modifications can potentially contribute to significant impairments in muscle quality (MQ) of the knee extensor muscles (Ivey et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The MQ, also known as specific tension, refers to force per unit of active mass (Ivey et al 2000;Lynch et al 1999) and has been suggested as a better indicator of muscle function than muscle strength alone (Dutta et al 1997), because it provides an estimate of the contribution of muscle hypertrophy and neuromuscular factors to changes in muscle strength (Castro et al 1995;Tracy et al 1999). Furthermore, the MQ seems to have a strong association with functional capacity in elderly people (Pinto et al 2014).…”
Section: Introductionmentioning
confidence: 99%